The Use of Augmented Reality 2.0 (AR 2.0) Application in Assisting Students to Draw 3D Orbitals - Aiza Mufida Mozi; Lee Eva (Malaysia Journal of Invention and Innovation, 2023)
The study aims to promote students’ independent learning by implementing the use of AR technology in Chemistry concepts, particularly in the topic of 3D orbitals. The AR 2.0 app “3D Molecular Shape” is an interactive mobile app which was developed using UNITY with C# language and further modified into version 2.0. It can be found and downloaded free of charge from Google Play Store. The upgraded AR 2.0 application provides QR code for scanning and user manual to follow. The process involves scanning the pre-generated QR codes via smartphones and enables students to visualize the 3D orbitals in AR views. This helps students to understand and draw the accurate 3D orbitals successfully. The analysis was carried out based on the pre- and post-test among pre-university students cohort 21/22. Respective sets of pre- and post-test questions were administered to the students. The data was collected and analyzed quantitatively using bar chart. From the analysis, a significant improvement shown by the students’ performances convinces that this AR app is able to assist students to understand better and draw 3D orbitals more accurately. Interviews and questionnaires were distributed and collected among the candidates to acquire their perception towards the use of AR 2.0 app “3D Molecular Shape” in supporting them to draw the 3D orbitals.